The clinical effects of red blood cell transfusions: an overview of the randomized controlled trials evidence base. - Wilkinson, K; Brunskill, S; Dorée, C; Hopewell, S; Stanworth, S; Murphy, M; Hyde, C (2011)
No up-to-date overview of randomized controlled trials (RCTs) in red blood cell (RBC) transfusion exists. This systematic review examines the quantity and quality of the evidence for the clinical effects of RBC transfusion. One hundred forty-two eligible RCTs were identified through searches of The Cochrane Library (issue 4, 2009), MEDLINE (1950 to November 2009), EMBASE (1974 to November 2009), and other relevant sources. After data extraction and methodological quality assessment, trials were grouped by clinical specialty and type of RBC transfusion. Data analysis was predominantly descriptive. The 142 RCTs covered 11 specialties and 10 types of RBC transfusion. The number of included patients varied widely across the RCTs (median, 57; IQ range, 27-167). Most trials were single center comparing 2 parallel study arms. Overall, the reporting of methodological assessment was poor, although it improved markedly from 2001. Clinical areas with few trials are highlighted. Comparison with a study of RBC use in clinical practice highlighted a lack of correlation between the size of the evidence base for a given clinical specialty and the proportion of total RBC use by that clinical specialty. The gaps in the evidence base and the poor methodology of trials particularly in the past do not provide a strong evidence base for the use of RBC transfusions, but they indicate important targets for future research.